PERANCANGAN APLIKASI E-COMMERCE PADA WARUNG BAKSO MAS ARI - Kristina Kristina; Kartono Kartono; Sylvia Deviyanti (LPPM Universitas Widya Dharma Pontianak, 2023)
The manual system is waiting for the service process at Warung Bakso Mas Ari because the small number of servants cannot serve customers who are busy on certain days. This system will run slower because the waiter must serve one by one and add all customer orders manually, so that it will improve the service process and correct calculation problems due to lack of accuracy. Computerized systems are needed so that employees can work optimally and service faster will help solve problems in calculations. Therefore, this study was conducted to discuss an application that can streamline employee work and more accurate calculations. The author uses descriptive research designs to make research, while the data collection method used is the study of literature that includes scientific books, scientific papers, scientific journals, theses, and sources that can be shared in various media. The system analysis technique used is object-oriented technique with Unified Modeling Language (UML) modeling. The design application uses the PHP programming language and MySQL database management system. This research resulted in a web-based sales application at Warung Bakso Mas Ari. Application designed to streamline employee work and more accurate calculations. Reports generated can be viewed through the report menu available in the application. With this application, it is expected to reduce calculation errors and improve employee work. The conclusion of this research is that the application built can streamline employee work and calculate sales totals more accurately. Suggestions from writers that can be given are using barcodes to add stock data, the system can be provided online, adding notification features. Keywords: Sales, Website, Restaurant